Pelatihan dan Workshop Promosi Digital Produk Unggulan BUMDES Sebagai Penggerak Ekonomi Masyarakat di Desa Waru Kecamatan Parung Kabupaten Bogor - Ahmad Maulidizen; Risman Nugraha; Abdul Haris Muctar; Muhammad Hasan Abdul Azis Naibaho; Muhammad Rafi Thoriq; Nuha Afifah Zuhri; Nur Rahmah Zakiyah (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Badan Usaha Milik Desa (BUMDes) functions as a tool to drive rural economic development by harnessing the potential within the village. One of the main obstacles in BUMDes development is the lack of quality human resources. The goal of this PKM program is to provide training and workshops to the management of BUMDes in Desa Waru, focusing on the digital promotion of BUMDes' flagship products. The method employed in this PKM consists of training and workshops, which involve the delivery of materials and practical applications. The subjects of this activity include 15 members of the BUMDes management in Desa Waru. The outcome of this PKM is that digital promotion of BUMDes' flagship products is a smart step in addressing current economic challenges. By leveraging digital potential, BUMDes can increase product visibility, boost sales, and contribute to the economic development of the village.